Epstein-Barr Virus and miRNAs: Partners in Crime in the Pathogenesis of Multiple Sclerosis? - Hassani, Asma; Khan, Gulfaraz (Frontiers in Immunology, 2019)
MicroRNAs (miRNAs) are small non-coding RNAs that modulate gene expression post transcriptionally. In healthy individuals, miRNAs contribute to maintaining gene expression homeostasis. However, the level of miRNAs expressed is markedly altered in different diseases, including multiple sclerosis (MS). The impact of such changes is being investigated, and thought to shape the immune system into the inflammatory autoimmune phenotype. Much is yet to be learned about the contribution of miRNAs in the molecular pathology of MS. Epstein-Barr virus (EBV) infection is a major risk factor for the development of MS. EBV encodes more than 40 miRNAs, most of which have been studied in the context of EBV associated cancers. These viral miRNAs regulate genes involved in cell apoptosis, antigen presentation and recognition, as well as B cell transformation. If EBV infection contributes to the pathology of MS, it is plausible that EBV miRNAs may be involved. Unfortunately, there are limited studies addressing how EBV miRNAs are involved in the pathogenesis of MS. This review summarizes what has been reported regarding cellular and viral miRNA profiles in MS and proposes possible interactions between the two in the development of MS.